A revision of the freshwater crabs (Crustacea: Decapoda: Brachyura: Potamonautidae) of the Lake Kivu drainage basin in Central and East Africa - Meyer, Kirstin S.; Cumberlidge, Neil (Zootaxa, 2011)
The taxonomy of the freshwater crabs living in the rivers draining from the mountains in the eastern Democratic Republic of the Congo and Rwanda into Lake Kivu is revised. Four species are recognized: Potamonautes perparvus (Rathbun, 1921), P. minor Bott, 1955, P. gonocristatus Bott, 1955, and P. semilunaris Bott, 1955. Updated diagnoses, illustrations, and distribution maps are provided for the species. The four species are compared to each other, and an identification key to all eight species found in Lake Kivu and its drainage basin is included.